Radicalized - new jihadists and the threat to the west - Neumann, Peter R. (I.B. Tauris, 2016)
The attacks in Paris in January and November 2015 heralded the beginning of a new wave of terrorism—one rooted in the ongoing conflict in Syria and Iraq. As ISIS seeks to expand its reach in the Middle East, its territory serves as a base for training and operations for a new generation of jihadis. Thousands of young people from the West, primarily from Europe, have travelled to join ISIS, re-emerging as hardened fighters with military training and a network of international contacts. Many of these have now returned to their homelands, where it is feared they are planning a new series of brutal attacks. Peter R. Neumann here explains the phenomenon of the 'new jihadis', and shows why the threat of terrorism in the West is greater than ever before. Based on interviews and previously-unseen material, Neumann provides an essential introduction to one of the greatest crises of our time. --Publisher